2005
DOI: 10.1103/physreva.71.015201
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of Na clusters embedded in a rare-gas matrix

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…On the theoretical part, recent work by Gervais et al 18 has shown that the surrounding matrix modifies slightly the geometry of the embedded cluster and therefore its electronic structure, changing its optical response. Moreover the presence of the matrix produces a confinement of the valence electrons of the cluster resulting in a blueshift of the transitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the theoretical part, recent work by Gervais et al 18 has shown that the surrounding matrix modifies slightly the geometry of the embedded cluster and therefore its electronic structure, changing its optical response. Moreover the presence of the matrix produces a confinement of the valence electrons of the cluster resulting in a blueshift of the transitions.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed, for example, in Ag 2 and Ag 3 . [15][16][17] Using quantum calculations on sodium clusters embedded in an argon matrix, Gervais et al 18,19 showed the possible coexistence of several site isomers with slightly different transition energies and intensities. The effect of the matrix is shown to be the result of two competing effects: the dielectric effect discussed above that leads to a redshift and a confinement of the valence electrons of the cluster leading to a blueshift.…”
Section: Introductionmentioning
confidence: 99%
“…5 The effect of the matrix induces small changes in the geometrical structure of embedding clusters, which may have a large influence on the oscillator strength of the different transitions. 10,43,44 Also symmetry forbidden transitions may be lifted by interaction with the matrix, we suggest that this is the case for Ag 4 and Ag 6 clusters in an argon matrix. The delocalized nature of the conduction electrons leads to isomers of close ground state energies.…”
Section: B Matrix Effects In Silver Clustersmentioning
confidence: 99%
“…We thus expect that different isomers are present in the matrix. Furthermore, the cluster stabilization energy differs from one matrix to the other 43,44 suggesting that the relative weight of different isomers depends on the embedding matrix. A detailed analysis indicates that these effects are present in the case of Ag 6 , Ag 8 , and Ag 9 clusters.…”
Section: B Matrix Effects In Silver Clustersmentioning
confidence: 99%
See 1 more Smart Citation